Articles - Monique Plamondon-Bouchard (Cahiers de géographie du Québec, 2005)
Observations of net radiation at Poste-de-la-Baleine (Great Whale) have shown that low cloud and fog are two important elements in the expianation of the climate along the South-East coast of Hudson Bay. Based on the hourly surface meteorclogical data for 1969, annual and seasonal frequencies have been established of the occurrence of low cloud and fog and their characteristics. From these frequencies, in association with other factors, it is possible to gauge to a certain extent the effect of low cloud and fog on the climate of Poste-de-la-Baleine (Great Whale).The results indicate that low cloud and fog were present at more than 50% of the observations in 1969, mainly during the period of daylight. Their high frequency, specially during the mild season, constitutes a dominant factor in the reduction of the energy available at the surface. Several consequences of their particular climatic conditions on human activities and on the vegetation are indicated. Des observations sur le bilan du rayonnement effectuées à Poste-de-la-Baleine, ont indiqué que les nuages bas et la brume sont des éléments très importants dans l'explication du climat de la région côtière du sud-est de la mer d'Hudson. À partir des données météorologiques horaires de 1969, on a établi des fréquences des nuages bas et de la brume, ainsi que de leurs caractéristiques pour l'année entière et par saison. Ces fréquences associées à d'autres éléments du climat, permettent de dégager l'influence des nuages bas et de la brume sur les conditions climatiques à Poste-de-la-Baleine.Les résultats indiquent que les nuages bas et la brume apparaissent pendant plus de 50% des heures d'observation en 1969 principalement durant la période diurne. Leur fréquence élevée, surtout durant la saison douce, constitue un facteur dominant de la diminution de l'énergie disponible en surface. On signale quelques conséquences des conditions particulières du climat sur les activités humaines et sur la végétation.